PENGARUH TEKNIK ECOPRINT TERHADAP KEMAMPUAN BERFIKIR KREATIF ANAK USIA DINI DI TK NEGERI PEMBINA KIHAJAR DEWANTORO KELOMPOK B KECAMATAN KOTA SELATAN KOTA GORONTALO - Tri Indriyani Suleman; Pupung Puspa Ardini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
ABSTRACT The problem in this study is whether there is an influence of the ecoprint technique on the creative thinking ability of children aged 5-6 years at TK Negeri Pembina Kihajar Dewantoro, Kota Selatan Subdistrict, Gorontalo City. This research was a quantitative experimental study with a pre-experimental design (one group pretest-posttest design). The results of the study with a sample size of 26 children showed an increase in the average pre-test and post-test scores. This can be seen from the pretest data, which had an average score of 19,19231 and a standard deviation of 4,621854. In contrast, the post-test data had an average score of 42,38462 and a standard deviation of 1 .651107. Based on the t-test from the paired test results, it was found that the sig. (2-tailed) value was 0,000, which is less than 0,05, meaning that Ho is rejected and Ha is confirmed. This means there is an influence of the ecoprint technique on the creative thinking ability of children aged 5-6 years at TK Negeri Pembina Ki Hajar Dewantoro, Kota Selatan Subdistrict, Gorontalo City.